Parks Under Stress: Air Temperature Regulation of Urban Green Spaces Under Conditions of Drought and Summer Heat - Kraemer, Roland; Kabisch, Nadja (Frontiers in Environmental Science, 2022)
In times of urbanization and climate change, urban green spaces and their ecosystem services are pivotal for adapting to extreme weather events such as heat and drought. But what happens to the provision of ecosystem services when green spaces themselves are compromised by heat and drought? In this study, we assessed the air temperature regulation by two structurally distinct inner-city parks in Leipzig, Germany, that were strongly affected by the heat and drought periods in 2018 and 2019. We used a dense network of in-situ measurements and machine learning to create spatially explicit maps of air temperature distribution at a fine-scale neighborhood level for a 24 h period during the summer heat wave in 2019. The results showed that the larger, tree-dominated park could maintain spaces of relative coolness at any time, whereas the other rather open, grass-dominated park was strongly heated during the daytime but provided relatively cool air during the night and early morning. We found a maximum spatially averaged cooling effect of green spaces versus the built-up surroundings of 1.1 °C in the morning. In the afternoon, however, when air temperatures peaked at nearly 40 °C, cooling was limited to shaded areas, leading to average differences between green spaces and built-up surroundings below 1 °C. Our spatially explicit maps indicated that the ‘cooling distances’ of green spaces, i.e., cooling effects that extend beyond the boundaries of a park, are negligible during dry and hot conditions. We conclude that vegetation structure, particularly the configuration of trees, is key to designing heat and drought-resilient green spaces and thus maintaining ecosystem service provision under the challenges of climate change. Urban planning needs to account for larger green spaces that are complemented by decentralized, well-distributed small-scale green infrastructure that intersperses the built infrastructure such as roadside greenery and vegetated backyards.